TOURISM TRANSFORMATION TOWARDS SUSTAINABILITY THROUGH INTELLIGENT AUTOMATION: A SYSTEMATIC REVIEW - Fitrianti, Nida Garnida; Padma Hanuun, nazh; Yolistina , Anggun (Yayasan Kreatif Indonesia Emas, 2024)
Transforming tourism towards sustainability through intelligent automation has become a key focus for many tourism destinations around the world. With the adoption of intelligent automation technology, the tourism industry has the potential to improve operational efficiency, environmental sustainability and tourist experience. However, this process is also faced with a number of obstacles, including high implementation costs, a lack of workforce skills, and concerns about the replacement of human jobs by technology. To overcome these obstacles, there needs to be effective policy support from the government, including fiscal incentives, workforce training, and regulations that balance innovation and protection. Tourism destination countries can adopt policy models such as national action plans for sustainable tourism, sustainable tourism policy forums, and public-private-academic partnerships to create an enabling environment for sustainable tourism transformation. With these steps, the tourism industry can harness the potential of intelligent automation technology to achieve sustainability goals while keeping the interests of local communities, the environment and long-term sustainability in mind.